HUBUNGAN ANTARA KEMAMPUAN NUMERASI DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV DI SEKOLAH DASAR KELURAHAN SUSUKAN - Zahwah, Kayla Khansa; Hasanah, Uswatun; Satibi Hidayat, Otib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between numeracy skills and mathematics learning outcomes of fourth-grade elementary school students in Susukan Village on the topic of multiplication and division of whole numbers. The problem identified in this study is the suboptimal mathematics learning outcomes of students, particularly in arithmetic operations, as well as a lack of research specifically examining numeracy skills at the fourth-grade level. This study employed a quantitative correlational approach. The population consisted of all fourth-grade students from three elementary schools in Susukan Village, with a total sample of 90 students selected through saturated sampling. Data were collected using a numeracy skills test in the form of contextual essay questions based on Polya's problem-solving stages, and a mathematics learning outcomes test in short-answer format. Both instruments were validated through expert judgment and Pearson Product Moment correlation, and reliability was assessed using Cronbach's Alpha. Normality testing using Kolmogorov-Smirnov showed that the data were not normally distributed (p < 0.05), so hypothesis testing was conducted using Spearman’s rho non-parametric correlation. The results showed a Spearman’s rho coefficient of 0.213 with a significance value of 0.044 (p < 0.05), indicating a significant positive relationship between numeracy skills and mathematics learning outcomes. The coefficient of determination (R² = 0.045) revealed that numeracy skills contributed 4.5% to the variance in mathematics learning outcomes, while the remaining 95.5% was influenced by other external factors.